Building self-esteem with adult learners - Lawrence, Denis (Paul Chapman Pub. ; SAGE Publications, 2000)
Research shows that self-esteem is a major factor in learning outcomes, particularly for adult learners engaged on courses to improve literacy skills. This text provides the theory and practical techniques to raise students' self-esteem.